1999
DOI: 10.1046/j.1440-1827.1999.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

P53 and proliferating cell nuclear antigen (PCNA) expression in non‐tumoral liver diseases

Abstract: The tumor suppressor gene p53 is known to be involved in the negative regulation of cell growth. Proliferating cell nuclear antigen (PCNA), which is a nuclear protein and a component of the DNA replication process, is also involved in growth regulation. Both have been studied as progression markers in various tumors including hepatocellular carcinoma. In the present study, the aberrant p53 protein and PCNA expressions in non-tumoral liver diseases were investigated. Using monoclonal antibodies anti-p53 (D07-DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
19
1
Order By: Relevance
“…Although others have reported that p53 activation itself coincides with fatty liver in humans (28), this is the first report to describe the role of p53 in the mechanisms of hepatocellular injury accompanied by hepatic steatosis.…”
Section: Discussionmentioning
confidence: 67%
“…Although others have reported that p53 activation itself coincides with fatty liver in humans (28), this is the first report to describe the role of p53 in the mechanisms of hepatocellular injury accompanied by hepatic steatosis.…”
Section: Discussionmentioning
confidence: 67%
“…Studies on TP53 alterations in normal liver samples demonstrated a linear relationship between incidence of mutations in the codon 249 and the extent of exposure to AFB1 [35]. Akyol et al in 21 different pathological entities of non-tumoral liver, demonstrated overexpression of p53 protein in 35% specimens, significantly more frequent in patients with steatohepatitis [32]. Studies in non-tumorous tissues of patients with Wilson's disease and hemochromatosis documented higher frequency of genetic aberrations (transversions and transitions) in both codons 249 and 250 of TP53 in the patients, as compared to healthy controls [34].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have dealt with incidence of genetic aberrations in TP53 in patients with non-neoplastic liver pathology or with risk factors prompting development of HCC (e.g. chronic viral infections) or the reports relate to selected exons of TP53 [32,34,35,40]. No mutations in the codon 249 were detected in North American patients with chronic hepatitis and/or liver cirrhosis as compared to 5/6 positive samples of non-neoplastic liver from Mozambican patients (HBV infection and AFB1 exposure) [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, it was shown before that p53 is involved in the molecular mechanisms leading to liver injuries (Blight et al, 2003;Schafer et al, 2003). Indeed, patients with various inflammatory liver diseases were found to accumulate p53 protein (Akyol et al, 1999;Panasiuk et al, 2006;Attallah et al, 2009). It has been also reported that p53 serum level was elevated in HBV-related cirrhosis patients (Shahnazari et al, 2014).…”
Section: Discussionmentioning
confidence: 98%